Design of Ergonomic Work Desk for Workbench Practicum - Kurnia Dwi Artika; Rusuminto Syahyuniar; Adhiela Noer Syaief (Logic : Jurnal Rancang Bangun dan Teknologi, 2019)
Polytechnics as vocational education that applies more mastery of ability in the field of technology by prioritizing 70% practicum and 30% theory. As for workbench practicum, it is one of the basic practicum in the Automotive Engineering Department. This practicum contains basic mechanical work that is within the scope of conventional machining. The problem is the ineffectiveness in conducting the practicum process, where facilities and infrastructure are minimal and far away from the reach of work equipment, thus inhibiting the bench work practicum process. So it needs to be conducted on ergonomic workbench by determined good body position or movement based on the RULA value. The results of the application of ergonomic bench design workbench related that with setting equipment in one table, worker position, and the use of equipment had a value of RULA was 4.